Students’ FLA and Their Perspectives on Translanguaging Practices in Indonesian EFL Classrooms - Mas’ud Madhani Sanjaya; Joko Nurkamto; Sumardi Sumardi (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
In non-English speaking countries, some teachers found it difficult to teach the target language in monolingualism because some of the learners felt anxious about learning English as a foreign language, or called foreign language anxiety (FLA), so teachers implemented translanguaging in their EFL classes. This paper explores students’ perspectives on pedagogical translanguaging and the point of view on whether the use of translanguaging is beneficial in the English foreign language (EFL) classroom and how translanguaging helps EFL learners through their FLA. The participants of this research are four students in a junior private Islamic school in Indonesia. The methodology of this research is qualitative, while the type of research used is a case study and analysis with thematic analysis. The findings of this paper are that students get more benefits when the teacher uses translanguaging in their class because it helps them understand the learning objectives, the teacher's instructions, and gives them the confidence to follow the English language learning without fear of misinterpretation. Translanguaging can manage and negotiate students’ FLA in the EFL classroom.